2021
DOI: 10.17221/56/2021-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Inferring customer heterogeneity for rural tourism: A latent class approach based on a best-worst choice modelling

Abstract: This research aims to analyse customers' preference heterogeneity for rural tourism in Spain and explore their preferences' personal and socio-demographic factors. To achieve this purpose, latent class analysis with the best-worst choice modelling has been applied through conducting a survey on 452 customers in Madrid and Barcelona. The results show that there are five classes in the Spanish rural tourism market: 'all-around seeker', 'leisure activist', 'culture explorer', 'comfort-driven user', and 'basic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(60 reference statements)
0
2
0
1
Order By: Relevance
“…It is also essential to communicate green values through quality labels on official accommodation websites [5]. Incorporating corporate social responsibility (CSR) can promote sustainable and inclusive growth, improve financial performance and competitiveness [60], and ultimately lead to greater customer loyalty [61] based on factors such as number of rooms, quality certification, and location [58]. In addition, fostering a strong sense of place and creating a satisfying tourism experience helps build a cognitive image of local identity, fostering consumer affection and loyalty to the destination [58,62].…”
Section: Digitalizationmentioning
confidence: 99%
“…It is also essential to communicate green values through quality labels on official accommodation websites [5]. Incorporating corporate social responsibility (CSR) can promote sustainable and inclusive growth, improve financial performance and competitiveness [60], and ultimately lead to greater customer loyalty [61] based on factors such as number of rooms, quality certification, and location [58]. In addition, fostering a strong sense of place and creating a satisfying tourism experience helps build a cognitive image of local identity, fostering consumer affection and loyalty to the destination [58,62].…”
Section: Digitalizationmentioning
confidence: 99%
“…Ianya berfungsi kepada kecenderungan atau kesanggupan serta rintangan yang dihadapi bagi mengadakan perjalanan. Di sini kesanggupan dan kemampuan seseorang individu dipengaruhi oleh kehendaknya sendiri iaitu motivasi (Seo et al 2019;Al Adwan 2020;Zhang & Walsh 2021;Iványi & Bíró-Szigeti 2021), kedudukan sosio-ekonomi (Yeh & Liu 2019;Promsivapallop & Kannaovakun 2020;Gavurova et al 2020;Švec et al 2021;An & Alarcón 2021), keberkesanan pemasaran dan promosi (Chrząścik 2019;Castañeda et al 2020;Korbiel 2021;Tinakhat 2021;Yim et al 2021) yang dilakukan. Pemasaran dan promosi penting terutama bagi meningkatkan permintaan jangka panjang di samping memberi pendedahan kepada masyarakat umum.…”
Section: Pengenalanunclassified
“…On these platforms, with the help of popular topics, hashtags, and other tools, the characteristics of rural tourism are skillfully conveyed, thus stimulating the interest of young people [8]. For the target group of middle-aged and elderly people, information can be disseminated through WeChat public numbers, online communities, and other platforms detailing the comfortable vacation experience so that they will be interested in rural tourism [9][10]. Guo, H. et al analyzed the conflicted relationship between social exclusion and rural tourism by taking Wuyuan Likeng Village as the research object and found that rural residents have different social exclusion at different social levels and should establish corresponding rural linkage mechanisms to strengthen the villagers' main position in rural tourism, so that the villagers can provide decision-making opinions in the development of rural tourism, and promote the high-quality development of rural tourism in order to reduce the social exclusion and conflict [11].…”
Section: Introductionmentioning
confidence: 99%